Exploring causal pathways amid complexity - Lynn, Jewlya; Apgar, Marina (Research Handbook on Program Evaluation, 2024)
Evaluation has a long history of using experimental and quasi-experimental designs to measure the effects of programs and strategies, and through this, to infer causality. Yet, these approaches are often not appropriate when evaluating change in complex, dynamic systems. Further, programs and strategies that seek to produce change in complex settings are increasingly common. This leads to an evaluation dilemma: if and how do evaluators attend to causality amid complexity? Too often, the answer has been to use causal thinking in the design of the evaluation and interpretation of findings, but not incorporate causal analysis and inference. In practice, this allows for assumptions about how change happens to go unchallenged. In this chapter, we explore the use of causal analysis through methods designed to attend to complexity and context, strengthened by participatory implementation, that can be implemented with rigor.
Section: Research Handbook on Program Evaluation

Bridging Learning and Action: How Did CLARISSA’s Participatory Adaptive Management Approach Foster Innovation, Effectiveness, and Stakeholder Empowerment? - Prieto Martin, Pedro; Apgar, Marina; Afroze, Jiniya; Arulanantham, Amit; Hicks, Jacqueline; Karki, Shanta; Mareschal, Sophie; Paul, Sukanta; Snijder, Mieke; Uddin, Forhad; Veitch, Helen (Institute of Development Studies, 2024)
Child Labour: Action-Research-Innovation in South and South-Eastern Asia (CLARISSA) is an evidence and innovation-generation programme funded by the United Kingdom’s Foreign, Commonwealth & Development Office (FCDO), responding to the challenge of the worst forms of child labour (WFCL) in Bangladesh and Nepal. It is a challenge characterised by a poor understanding of its drivers and a lack of evidence on what works to combat it. To handle such fundamental uncertainty, the programme adopts a child-centric and participatory action research approach, which is supported by an adaptive management model to respond better to challenges and opportunities. From its inception, the programme needed to navigate shocks and challenges, such as Covid-19 lockdowns, political upheaval, and sustained budget cuts, which put its capacity to learn and evolve to the test. This paper shares insights emerging from evaluating CLARISSA’s participatory adaptive management (PAM) practices, connecting them with current discussions on adaptive management. It provides an in-depth evaluation of CLARISSA’s PAM approach, exploring how adaptive strategies were implemented and evolved throughout the programme’s life cycle. Multiple cases of adaptation and misadaptation were selected and analysed through a series of in-depth interviews and review of programme documentation, allowing us to assess whether and how the adaptive management practices have been operationalised, the degree to which they led to enhanced decision-making and effectiveness, and their empowering effect on children and other programme stakeholders. Through conceptual analysis and real-world examples, the paper examines the key stages and critical dimensions of PAM, conveying the complexities and dynamism of adaptive management in development work, while highlighting both the successes and challenges encountered in operationalising PAM within CLARISSA.
Accepted: 2024-05-10T08:21:46Z